Leprechaun in late winter - Osborne, Mary Pope.; Murdocca, Sal (New York : Random House, 2010)
Jack and Annie travel back to nineteenth-century Ireland to inspire a young Augusta Gregory to share her love of Irish legends and folktales with the world.
"A Merlin Mission."
"A stepping stone book."
3.8
3-6
Keywords: Time travel -- Juvenile fiction; Magic -- Juvenile fiction; Tree houses -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Gregory, -- Lady, -- 1852-1932 -- Juvenile fiction; Ireland -- History -- 19th century -- Juvenile fiction; Time travel -- Fiction; Magic -- Fiction; Tree houses -- Fiction; Brothers and sisters -- Fiction; Gregory, -- Lady, -- 1852-1932 -- Fiction; Ireland -- History -- 19th century -- Fiction; Time travel -- Fiction; Magic -- Fiction; Tree houses -- Fiction; Siblings -- Fiction; Gregory, -- Lady, -- 1852-1932 -- Fiction; Ireland -- History -- Fiction